Interval optimal scheduling of integrated electricity and district heating systems considering dynamic characteristics of heating network - Chen, Houhe; Zhang, Ting; Zhang, Rufeng; Jiang, Tao; Li, Xue; Li, Guoqing (Energy systems integration, 2020)
Coordinated operation of integrated electricity and district heating system (IEDHS) has great potential to enhance the flexibility of the power system to cope with the wind power curtailment. This study proposes an interval optimal scheduling algorithm for IEDHSs, considering the dynamic characteristics of the heating network. The model of the district heating system with dynamic characteristics including transmission delay and heat losses, is established in detail, and the uncertainties of both wind power and electricity and heating loads are described with interval numbers. Then an interval optimal scheduling model of the IEDHS is formulated to minimise the IEDHS operation cost. The impacts of the transmission delay and heat losses of the heating network on the scheduling of the IEDHS are analysed. Case studies are performed on the PJM 5‐bus electricity system with a 6‐node district heating system and IEEE 39‐bus electricity system with a 12‐node district heating system to evaluate the effectiveness of the proposed model. The results demonstrate that the dynamic characteristics of the heating network can integrate more wind power and enlarge the width of the cost interval.